Influence of outsole design on centre of rotation during turning movements - Driscoll, H.; Kirk, B.; Koerger, H.; Haake, S. (Procedia Engineering, 2012)
A bespoke 3D measurement system was used to investigate the influence of the outsole configuration on the centre of rotation during a movement used by football players to change direction. Five outsole configurations were selected for analysis ranging from rounded studs to bladed designs. High-speed video information and force-plate data were collected and analysed to obtain the shoe kinematic and kinetic results. The centre of rotation was calculated during shoe-surface contact using the location of the stud positions on the outsole. Results indicated that significant differences occurred between outsole designs for the kinetic data, but all shoes impacted the ground at a similar orientation. The resulting centre of rotation varied between designs, but on average was located towards the toe of the shoe. This differs from the centre of rotation often used in traction testing and as a result, may influence the veracity of current assessment techniques.